New Heterobimetallic Ferrocenyl Dithiophosphonato Cd(II) and Hg(II) Complexes: DNA Interactions, Antimicrobial and Anticancer Activity Studies of the Cd(II) Complexes - SAĞLAM, ERTUĞRUL GAZİ (WILEY-V C H VERLAG GMBH, 2021)
A series of new ferrocenyldithiophosphonato complexes of Cd(II) and Hg(II) ions were synthesized and characterized by spectroscopic methods. The antiproliferative activities of the ligands and their Cd(II) complexes were screened against four human cell lines using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) method. While the ligands were inactive in the three cancer cell lines screened, their Cd(II) complexes showed a very toxic effect against all cell lines. The complexes especially demonstrated the highest efficacy in the breast cancer cell line among the others. They were found to have higher cytotoxic activity compared to positive controls used in all cell lines. Furthermore, the ligands and their Cd(II) complexes were tested for antimicrobial activity against some pathogen bacteria and yeast strains. The minimum inhibitory concentration (MIC) and minimal bactericidal concentration (MBC), values were found to be in the ranges of 39.06-612 mu M and 39.06-1250 mu M, respectively. Besides, interactions between the compounds and plasmid DNA were studied by agarose gel electrophoresis. All of these cleaved double-strand supercoiled plasmid DNA at the highest concentration indicating DNA cleavage activity. The restriction enzyme digestion of the compound-DNA mixtures showed that compounds bind to A/A and G/G nucleotides.
Keywords: Antimicrobial activity; Antiproliferative activity; Cadmium; mercury ferrocenyl-dithiophosphonate; Cytotoxicity; DNA interaction; Organo-dithiophosphorus compounds; CRYSTAL-STRUCTURE; STRUCTURAL-CHARACTERIZATION; COORDINATION CHEMISTRY; ANTIBACTERIAL ACTIVITY; NICKEL(II) COMPLEXES; LIGANDS; FC